Hand in hand evolution of boson heat capacity anomaly and slow β-relaxation in La-based metallic glasses. (15th May 2016) - Huang, B.; Zhu, Z.G.; Ge, T.P.; Bai, H.Y.; Sun, B.A.; Yang, Y.; Liu, C.T.; Wang, W.H.
Abstract: Glassy materials lacking the periodicity of crystals possess varieties of dynamic behaviors. Boson peak and slow β -relaxation (or Johari–Goldstein β -relaxation) preceding the α -relaxation are the two intrinsic and markedly different dynamic behaviors of glasses, and their structural origins are long-standing issues. Through alloying a model La-based metallic glass (MG) with different types of elements we find that the low-temperature boson heat capacity anomaly evolves hand in hand with high-temperature slow β -relaxation associated with free volume. With the free volume model and the generalized Maxwell model describing the heterogeneous structure, we demonstrate that the slow β -relaxation of MGs is a series of localized microscopic flows, which naturally develops from defective regions where boson peak arises. The coupling of boson peak and slow β -relaxation indicates their common structural origin of localized loosely packed regions in MGs. Graphical abstract: